Experimental Dielectric Measurements for Cost-fewer Polyvinyl Chloride Nanocomposites - Ahmed Thabet; Youssef Mobarak (Institute of Advanced Engineering and Science, 2015)
Polymer nanocomposites possess promising high performances as engineering materials, if they are prepared and fabricated properly. In this research, it has been processed samples of nanocomposite polymers as electrical insulating materials for application on the electric power cables by using the latest techniques of nanotechnology. This paper has been investigated enhanced dielectric and electrical properties of Polyvinyl chloride PVC as matrix have shown that trapping properties are highly modified by the presence of costless nanofillers clay and fumed silica. An experimental work for dielectric loss and capacitance of the new nanocomposite materials have been investigated and compared with unfilled industrial materials. It is found that a good correlation exists in respect of capacitance and dielectric loss values measured with percentage of nanofillers. Thus, it has been investigated the influence of costless nanofillers material and its concentration on dielectric properties of industrial polymers-based composite systems. A comparative study is performed between the unfilled base polymers, the systems containing one type of nanoparticles clay or fumed silica inside the host polymer with various concentrations.